THE EFFECT OF THE VAK LEARNING MODEL ON THE READING COMPREHENSION ABILITY OF GRADE III ELEMENTARY SCHOOL STUDENTS - Agustina Rahmawati; Prabawati Nurhabibah; Widia Nur Jannah (Universitas Majalengka, 2026)
This research is motivated by the low reading comprehension ability of elementary school students, especially in determining the main idea, understanding the meaning of reading, andThis research is motivated by the low reading comprehension ability of elementary school students in determining the main idea, understanding the content of the reading, and concluding information. This study aims to describe changes in students' reading comprehension skills after the implementation of the Visual, Auditory, and Kinesthetic (VAK) learning model in grade III students of SDN 2 Tegalwangi. The study used a quantitative approach with pre-experimental methods and a one-group design before and after treatment. The research subjects amounted to 37 students. Data collection techniques are carried out through observation, tests, and documentation. Data analysis used the Wilcoxon test and the calculation of improved learning outcomes. The results showed that the average score of students increased from 67.30 to 89.19. The results of the Wilcoxon test obtained a significance value of 0.000 < 0.05 which showed a difference in reading comprehension skills before and after learning. The results of the calculation of the improvement of learning outcomes obtained an average score of 0.6739 in the medium category, while the observation results showed that student involvement was in the very good category. Thus, the implementation of the VAK learning model shows changes in students' reading comprehension skills and supports student involvement during learning. concluding the content of the text. This study aims to determine the influence of the Visual, Auditory, and Kinesthetic (VAK) learning model on the reading comprehension ability of grade III students of SDN 2 Tegalwangi. This study uses a quantitative approach with a pre-experimental method and a one group pretest-posttest design. The research subjects amounted to 37 grade III students. Data collection techniques are carried out through observation, tests, and documentation. The results showed that the average pretest score of 67.30 increased to 89.19 in the average posttest score. The results of the Wilcoxon Signed Rank Test obtained a significance value of 0.000 < 0.05 which shows a significant influence of the VAK learning model on students' reading comprehension skills. In addition, the results of the N-Gain test obtained an average value of 0.6739 in the medium category. The application of the VAK learning model helps students to be more active in learning activities through direct seeing, listening, and doing activities so that students can more easily understand the content of reading. Thus, the Visual, Auditory, and Kinesthetic (VAK) learning model can be used as an alternative learning to improve elementary school students' reading comprehension skills.